Self-determination in secondary school students and their relationship with emotional intelligence and support for autonomy - Gómez-López, Manuel; Mendoza-Castejón, Daniel; Frías-López, Daniel; Manzano-Sánchez, David (Frontiers in Psychology, 2025)
IntroductionIn secondary education, a period characterized by multiple psychological, behavioral, and social changes in young people, academic motivation tends to decrease. This study focuses on physical education (PE) classes as a key space to positively influence students' motivation and emotional development, based on the Self-Determination Theory (SDT). This theory emphasizes the importance of satisfying three basic psychological needs (BPN): competence, autonomy, and social relationships, which in turn favor intrinsic motivation (IM) and emotional wellbeing.MethodsThe study included 502 students (11-18 years old) and explored the relationship between motivational profiles high profile (19.7%), low profile (29.3%), and moderate profile (51%) and emotional intelligence (EI) and the perception of autonomy.ResultsThe results revealed that high self-determination profiles were associated with higher levels of IM, satisfaction of basic needs, and emotional wellbeing, while low self-determination profiles showed a motivation and negative consequences such as dissatisfaction and lower performance. In addition, it was observed that girls tended to present profiles of greater self-determination compared to boys (residual effect = 4.1), and that extracurricular sports practice was positively related to more self-determined motivational profiles (residual effect 7.7 and 7.5 in high and moderate self-determination profiles).DiscussionThe findings highlight the need for adapted pedagogical strategies that promote autonomy, a positive climate and gender equity to maximize the positive impact of PE classes on the integral development of adolescents. In conclusion, PE classes can play a crucial role in improving student motivation and wellbeing if they are structured in a way that supports BPN and fosters an inclusive and motivating learning environment.